2010
DOI: 10.1016/j.cell.2010.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Virus-Plus-Susceptibility Gene Interaction Determines Crohn's Disease Gene Atg16L1 Phenotypes in Intestine

Abstract: SUMMARY It is unclear why disease occurs in only a small proportion of persons carrying common risk alleles of disease susceptibility genes. Here we demonstrate that an interaction between a specific virus infection and a mutation in the Crohn’s disease susceptibility gene Atg16L1 induces intestinal pathologies in mice. This virus-plus-susceptibility gene interaction generated abnormalities in granule packaging and unique patterns of gene expression in Paneth cells. Further, the response to injury induced by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
770
3
11

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 809 publications
(809 citation statements)
references
References 71 publications
25
770
3
11
Order By: Relevance
“…A20 deficiency in IECs does not cause spontaneous Paneth cell defects, but sensitizes their apoptotic loss in inflammatory conditions, either by direct low-dose TNF exposure or by exposure to cytokines produced by hyperactive A20-deficient myeloid cells, including TNF and IFNg. Both these cytokines are well known for their cytotoxic activities on IECs and may contribute to the development of intestinal inflammation through their direct activity on Paneth cells [39][40][41] . Also goblet cells are severely affected in A20 IEC/myel-KO mice, compromising the protective epithelial mucus layer.…”
Section: Discussionmentioning
confidence: 99%
“…A20 deficiency in IECs does not cause spontaneous Paneth cell defects, but sensitizes their apoptotic loss in inflammatory conditions, either by direct low-dose TNF exposure or by exposure to cytokines produced by hyperactive A20-deficient myeloid cells, including TNF and IFNg. Both these cytokines are well known for their cytotoxic activities on IECs and may contribute to the development of intestinal inflammation through their direct activity on Paneth cells [39][40][41] . Also goblet cells are severely affected in A20 IEC/myel-KO mice, compromising the protective epithelial mucus layer.…”
Section: Discussionmentioning
confidence: 99%
“…36,63,64 Here, we directly demonstrated aggravated experimental colitis in myeloid cell-specific autophagy-knockout mice, leading to increased mortality. In addition, we observed apparently increased colonic tissue expression of pro-Il1b and Il6 that are important players in colitis of DSS-treated Atg7 cKO mice compared to Atg7 cWT mice, [36][37][38] while the induction of Il6 was marginal.…”
Section: Figure 7 Systemic Inflammation and Bacterial Invasion Aftermentioning
confidence: 99%
“…Ultimately, this defi ciency results in defects in antigen presentation through the major histocompatability complex, decreased immune activation, and increased bacterial persistence in the gut mucosa ( 38 ). Recent in vivo murine studies demonstrate that the abnormal Paneth cell phenotype found with defective ATG16L1 function is the result of specifi c infection with a murine noravirus species, showing requisite genetic / microbial interactions that have important implications for human Crohn ' s disease ( 39 ).…”
Section: Host Genetic Defects In Containing Commensal Microbiotamentioning
confidence: 99%